PENGARUH PRODUCT QUALITY, PERCEIVED PRICE, DAN PROMOTION TERHADAP CUSTOMER SATISFACTION - Pratama, Ahmad Zaki; Prabandari, Sri Palupi (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
In the era of competition, competition between companies is getting tougher in every company to observe and know the wants and needs of consumers. This research aims to identify and analyze the effects of product quality, perceived price, and promotion on the satisfaction of Eiger customers in Malang. This research uses quantitative research with descriptive verification approach. Using purposive sampling method, 116 students of Universitas Brawijaya who have made at least one purchase of Eiger products. The data was harvested from questionnaires, library research, and web browsing and was analyzed using multiple linear regression in SPSS 25. This study finds that product quality, perceived price and promotion partially influence customer satisfaction. Product quality, perceived price and promotion explain 61,3% of the customer satisfaction, the remaining 38,7% is explained by other variables not included in this research. The implementation of product quality, perceived price, and promotion on Eiger products in the city of Malang is classified as very good and very good in creating customer satisfaction.